Magnetic field sensor based on magnetic fluid-infiltrated phase-shifted fiber Bragg grating - Bao, Lifeng (2020)
A novel magnetic field sensor based on a magnetic fluid (MF)-infiltrated phase-shifted fiber Bragg grating (PS-FBG) is proposed and experimentally demonstrated. The PS-FBG is formed by two FBG sections with a micrometer-level gap between them which is filled with microfluidic MF. External magnetic field changes refractive index and transmittance of the MF, leading to a magnetic-field-sensitive phase shift and hence wavelength shift of the transmission peak. Optical measurement of magnetic field strength is therefore achieved with a sensitivity of 2.42 pm/Oe within a range up to 120 Oe by monitoring wavelength shift of transmission spectrum of the MF-infiltrated PS-FBG. The micrometer-level action length of MF in this proposed sensor not only greatly reduces the consumption of MF but also brings forth a good potential for point detection of magnetic field distribution.